Vegan Alternatives to Processed Cheese and Yogurt Launched in the European Market during 2020: A Nutritional Challenge? - Fatma Boukid (MDPI AG, 2021)
Vegan alternatives to cheese (VAC) and yogurt (VAY) are fast-growing markets in Europe due to the increasing interest in plant-based alternatives to dairy products. This study aimed to take a closer look at the year 2020 and accordingly retrieved the nutritional information of dairy cheese and yogurt and their vegan counterparts for comparison. It was found that VAY (n = 182) provide more energy, total fats, and carbohydrates than dairy yogurt (n = 86), while saturated fatty acids (SFAs), sugars, and salt were not different between the two categories. Compared to dairy products (25.6%), 72.9% of the alternative products were declared low/no/reduced allergen, hence providing a larger spectrum of products to respond to consumers’ requirements. VAC (n = 114) showed high versatility of form compared to dairy (n = 115). Nutritionally, VAC have higher total fats, SFAs, and carbohydrates, but lower protein, salt, and sugar than dairy cheese. Food developers will continue to look for clean label solutions to improve the nutritional values of vegan products through the incorporation of natural ingredients, besides enhancing their taste and texture to appeal to flexitarians.